Penerapan Permainan Kartu Angka dalam Meningkatkan Kemampuan Mengenal Angka pada Anak Usia Dini di TK Aba Baraka - Angraeni, Putri; Latuconsina, Nur Khalisah; Tayeb, Thamrin; Patiung, Dahlia; Baharuddin, Baharuddin (NANAEKE: Indonesian Journal of Early Childhood Education, 2025)
The development of number recognition skills is one of the fundamental aspects of early mathematical readiness in young children. Efforts to enhance this ability must be carried out through engaging, contextual learning approaches that align with children’s developmental characteristics. Based on these needs, this study aims to describe children’s number recognition skills through the implementation of a number-card game in Class B1 at TK ABA Baraka and to compare the results with children in Class B2 who did not use this learning medium. This research employed a quasi-experimental method with a population of 36 children. The sample consisted of 16 students in Class B1 as the experimental group and 16 students in Class B2 as the control group. The research instrument was an observation sheet, and the data were analyzed using descriptive and inferential statistics. The results showed a significant increase in number recognition skills among children in the experimental class, with the average score rising from 48.31 (pre-test) to 94.37 (post-test). Meanwhile, the control class experienced a smaller increase, from 38.37 to 61.87. The Mann–Whitney U test indicated a significant difference between the two groups. Therefore, the use of number-card games is proven to be effective in improving number recognition skills in early childhood.